Relationship Between Perceptions Of Flu Advertisement With Self-Medication Behavior In The Community Of Sungai Besar Sub-District, Banjarbaru Selatan - M. Andi Chandra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Flu is one of the diseases that can be treated with self-medications, and information about these drugs is often obtained through advertisements on television, which will influence self-medication behavior. The purpose of this study was to analyze the relationship between perceptions of cold medicine advertisements and self-medication behavior using cold medicines. The method used in this study was an analytic survey with a cross-sectional research design and the sampling technique used was quota sampling. The sample of this study was 94 respondents with the majority of sample aged 17-27 years, female, high school/vocational high school graduates, who work as housewives. The results showed that respondents' perceptions of drug advertisements in self-medications were 10.64 % of respondents were affected and 89. 36 % of respondents were not affected. The self-medication behavior done by the respondents was 65.96% rational and 34.04% irrational. The results of the chi-square analysis showed that there was no significant relationship between perceptions of cold medicine advertisements and self-medication behavior using cold medicines (p value = 0.225). The results of the evaluation and the completeness of advertisements for cold medicine on television showed that some advertisements for cold medicines broadcast on television were still incomplete and inappropriate. The importance of rational use of medications should be a guide in all self-medication for the safety and maintenance of public health.